Berufliche Mobilität zur Anpassung struktureller Diskrepanzen am Arbeitsmarkt - Johannes Velling; Stefan Bender (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
Based on a theoretical model, the occupational mobility at the West German labor market is empirically investigated. For this purpose, an own concept of occupational mobility is developed. Using a multivariate proportional hazard cox model, several influential variables of occupational mobility are determined. The probability of an occupational change decreases with age, a better occupational status, and the size of the firm. A longer time of non-employment as well as a higher risk of unemployment makes a change of occupation more likely. Employees who change only occupation but stay in the same firm differ from simultaneous interfirm and interoccupational movers with respect to the influence of the wage and the size of the firm. The past duration of employment in the same occupation has a negative impact on occupational mobility, however this impact becomes insignificantly as the relative frequency of past changes is also included in the estimation. The wage differential between past and present occupation is largest for men and young employees. It decreases with the duration of employment in the same occupation, the duration of non-employment and the relative frequency of past changes. The purchase of an additional qualification (university, foreman degree) leads to a higher wage after occupational change. A simultaneous change of the firm increases wages the larger the new firm relative to the old firm. Occupational change within the same firm leads to higher wages with increasing firm size.
Keywords: 330